SAHAM DAN PASAR MODAL SYARIAH : KONSEP, SEJARAH, DAN PERKEMBANGANNYA - Fadlillah; Achmad Tarmidzi Anas; Badrut Ali; Badrus Sofi; Lukman; M. Samsul Arifin (STAI AN-NAJAH INDONESIA MANDIRI, 2023)
The Shariah capital market is growing, as demonstrated by the rise in the stock index in the Jakarta Islamic Index (JII). This index collects the price of shares of thirty companies that conform to the Islamic shariah and uses a scale of performance based on the sharia, one of which is the beta of sharial shares. Therefore, this study aims to analyze Sharia capital markets, including stocks. This empirical research uses purposive sampling techniques. Data obtained through the analysis of companies whose shares are listed on the Jakarta Islamic Index. History, Ideas, and Development of the Stock Market and the Syri'ah This is an attempt to provide a description of the capital market and limited stocks from a Syrian point of view. Therefore, this study aims to explain how it is applied in the financial sphere in other countries such as the United States, Malaysia and Indonesia. Keywords: Capital Market, Shares, Sharia Finance References Agutianto, “ Mengenal Konsep Pasar Modal Syari’ah,’ http:// agustianto. niriah.com/2008/04/30 mengenal konsep-konsep pasar modal syari’ah. Ahmad Kamil , M. Fauzan , Kitab Undang-Undang Hukum Perbangkan dan Ekonomi Syari’ah, (Jakarta: Kencana,2007), 756 Ayub, M. (2007).